2022
DOI: 10.3390/ijms23158364
|View full text |Cite
|
Sign up to set email alerts
|

Statins Neuromuscular Adverse Effects

Abstract: Statins are drugs widely prescribed in high-risk patients for cerebrovascular or cardiovascular diseases and are, usually, safe and well tolerated. However, these drugs sometimes may cause neuromuscular side effects that represent about two-third of all adverse events. Muscle-related adverse events include cramps, myalgia, weakness, immune-mediated necrotizing myopathy and, more rarely, rhabdomyolysis. Moreover, they may lead to peripheral neuropathy and induce or unmask a preexisting neuromuscular junction dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Few noninvasive techniques exist to accurately diagnose SAMS. 7,18 The most used biomarker is the CK enzyme, commonly employed as a marker of muscle damage. 28 Although our results showed that there were no differences between groups regarding CK values, there is a clinical consensus that alterations may (or may not) appear at any time during statin treatment, with the most common time for CK elevation being between the first and sixth month after the start of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Few noninvasive techniques exist to accurately diagnose SAMS. 7,18 The most used biomarker is the CK enzyme, commonly employed as a marker of muscle damage. 28 Although our results showed that there were no differences between groups regarding CK values, there is a clinical consensus that alterations may (or may not) appear at any time during statin treatment, with the most common time for CK elevation being between the first and sixth month after the start of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…After days to weeks of stopping the medicine, patients feel better, and their serum CK levels return to normal. The statins considered to have the least side effects on a muscular level are pravastatin and fluvastatin [ 92 , 95 ].…”
Section: Role Of Statins In Managing Dyslipidemiamentioning
confidence: 99%
“…9 Severe muscle damage, also known as rhabdomyolysis, is a rare but serious side-effect of statins. 10 Furthermore, statin use is associated with lower physical activity among community-dwelling older adults. 11 However, other studies failed to detect consistent changes in muscle contractile function and exercise performance in statin users.…”
Section: Introductionmentioning
confidence: 99%